'War to the knife'? The Anglican Clergy and Education at the End of the First World War. (3rd June 2019) - Smith, Mark
Abstract : In 1918 Charles Gore, the bishop of Oxford, issued queries preparatory to an episcopal visitation, including a series of questions about the future of church schools and religious education more generally. Coming some sixteen years after the restructuring of the dual system of state- and church-supported education by the Balfour Education Act of 1902, this material yields valuable insights into the views of approximately six hundred clergy regarding the successes and dysfunctions of the system at parish level. Set within the context of recent historiography on the trajectory of English Christianity in the1920s, this article uses this material to discuss the clergy's views on the value and purposes of school-based religious education, the prospects for sustaining these after almost four years of war and the compromises that might be required in order to preserve them.